Perancangan Accommodation Ladder And Gangway Portable Kapasitas 1 Ton Sebagai Sarana Penunjang Akses Akomodasi Kapal - Moch.Izzul Fikri Hidayah; Budianto Budianto; Hariyanto Soeroso (Proceedings Conference On Design Manufacture Engineering And Its Application, 2019)
Abstract – Among shipyard repair companies there is a constraint, which is the condition of the workarea that requires a tool or equipment that can be used to accommodate ship access which can reachdifferent height of the deck from the ship caused by tides. Even though there is existing product, theconditions often a fixed stairs which can cause rapid corrosion due to direct contact with the weather.Therefore, based on the mentioned problem, it is necessary to design a new lifting tool that can avoidthose problems. In this research, the new lifting tool design is called an Accommodation Ladder andGangway Portable. This equipment are not fixed and can be adjusted in terms of height whichdirectly can solved the problem at the deck area. Several steps will be carried out which will includedata to be appointed, lifting equipment planning, strength analysis and also the assembly processesfor the prototype. In order to meet the strength of the staircase restraint, it is necessary to analyze thestrength of the structure using the finite element method. After analysis, the FEM stress value wassmaller than the permissible stress, which means that it's acceptable and safe with the ratio of 166.67N/mm2 ? 157.2 N/mm2. For the lifting system in the lifting process, it was planned to use 16x9 1fcWire Rope with a diameter of 10 mm using 2 pulleys with a diameter of 100 mm. This operation usesa manual winch and it can be portable by using the High Duty Wheel.